IMPLEMENTASI MODEL ATIK DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK DALAM MENYUSUN POLA ABCD-ABCD - Halifa Rahakbauw; Sri Watini (Jurnal Buah Hati, 2022)
This study aims to improve cognitive abilities in children, especially the ability to compose ABCD-ABCD patterns. This happens because the initial observations made when the child is in school, the child's cognitive ability in compiling the ABCD-ABCD pattern is still low. The model used in this study is a classroom action research (CAR) model with the Arikunto model design through two cycles. Each cycle consists of 4 meetings. The subjects of the study were group B2 students aged 5-6 years at the RA Bina Insan Nusantara Manokwari institution with a total of 12 children consisting of 3 boys and 9 girls. The instruments used are observation sheets, photo documentation of children's work, performance. The results showed an increase in students' ability to compose the four ABCD-ABCD patterns. Before being given the action (pre-action) the child's ability to compose patterns was 83.3% in the sufficient category and only 16.7% in the good category. After being given action in Cycle I, namely by using the ATIK method, there was an increase in ability of 66.6% with good category. This means that there is an increase of 16.7%. At the end of the second cycle, it increased to 83.3% with good category. The success of this research if it reaches 80% in the good category. Thus, it can be said that the application of the ATIK method has succeeded in increasing children's cognitive abilities, especially in compiling the ABCD-ABCD pattern. Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan kognitif pada anak yaitu pada khususnya pada kemampuan menyusun pola ABCD-ABCD. Hal ini ini disebabkan hasil pengamatan awal yang dilakukan pada saat anak di sekolah kemampuan kognitif anak dalam menyusun pola ABCD-ABCD masih rendah. Model yang digunakan dalam penilitian ini merupakan model penilitian tindakan kelas (PTK) dengan desain model Arikunto melalui dua siklus. Setiap siklusnya terdiri dari 4 pertemuan. Subjek penilitian adalah siswa kelompok B2 usia 5-6 tahun pada lembanga RA Bina Insan Nusantara Manokwari sebanyak 12 anak terdiri dari 3 laki-laki dan 9 perempuan.. Instrumen yang digunakan berupa lembaran observasi, hasil dokumentasi foto hasil karya anak, unjuk performance. Hasil penelitian menunjukkan adanya peningkatan dalam kemampuan menyusun empat pola ABCD-ABCD dari siswa. Sebelum diberi tindakan (pratindakan ) kemampuan anak dalam menyusun pola sebesar 83,3 % pada kategori cukup dan hanya 16,7 % pada kategori baik. Setelah diberi tindakan pada Siklus I yaitu menggunakan metode ATIK, terjadi peningkatan kemampuan sebesar 66,6 % pada kategori baik. Artinya terjadi peningkatan 16,7 %. Pada akhir siklus II meningkat menjadi 83,3 % pada kategori baik. Keberhasilan penelitian ini bila mencapai 80 % pada kategori baik. Dengan demikian dapat dikatakan bahwa penerapan metode ATIK berhasil meningkatkan kemampuan kognitif anak khusunya dalam menyusun pola ABCD-ABCD.